Measuring patent quality in international comparison: Index development and application to China - Philipp Boeing; Elisabeth Mueller (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
We develop an index that compares the quality of Patent Cooperation Treaty (PCT) applications by considering citations generated by International Search Reports (ISRs). In its most restrictive variation, i.e. excluding citations from the home country and self-citations, the ISR index is not biased by selectivity in filing strategies, differences in citations due to varying national examination procedures, or domestic economic policies. Against the background of strong increases in Chinese patenting between 2001 and 2009, we compare the quality of Chinese PCT applications with those from high-income countries. Chinese PCT applications achieve only 34% of the quality level of international PCT applications. In addition, their quality is decreasing over time. We find that the patent quality of firms increases in R&D stocks but decreases with the introduction of PCT subsidies. Our results confirm that China's expansion of international filings was achieved to the detriment of quality.
urn:nbn:de:bsz:180-madoc-396610
Keywords: O34; O32; 330; patent quality; PCT system; China